Sustainable urban development in the context of ecotourism (Case study: an eco-lodge near the lakes of Wadi El-Rayan in Fayoum, Egypt) - Huda ALBaz (JES: Journal of Engineering Sciences)
The past decades have witnessed increasing interest and demand for ecotourism, and the world today faces increasing urban and environmental challenges, especially in areas adjacent to lakes and natural reserves in Egypt, where urban development is a major source of greenhouse gas emissions and pollution of various kinds, which contributes to the exacerbation of many environmental issues. The most important issues of the research came in the many challenges of urban development near the lakes and how to face these challenges and their impact on tourism, the blue economy in particular, the environment and society, and the problem also in the presence of natural reserves in Wadi Al-Rayyan that are threatened with degradation due to many development projects that lack sustainable urban planning and design. The research focused on the biggest risks that buildings will be exposed to near natural lake reserves in Egypt due to increased carbon emissions, and the importance of the research came in using the green building strategy in natural reserves in the project of ecological lodges near the lakes, and addressing the risk. The research aims to analyse the eco-lodge project from the perspective of sustainable urban development in the context of ecotourism in nature reserves by identifying the opportunities, challenges, threats, strengths and weaknesses facing the proposed project. The research tools were used to evaluate the project using LEED BD+C/New Construction (V4) standards,